SERVICE QUALITY AND STORE DESIGN IN RETAIL COMPETITIVENESS: (A CASE STUDY ON KOPI KENANGAN CIREBON CITY) - Riki Radiyansyah; Adi Setiawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The development of the coffee shop industry in Indonesia is experiencing very rapid growth, so that competition between brands is increasingly fierce and requires companies to have a competitive advantage. In the context of modern retail, customers not only consider product quality, but also service experience and convenience of store design. This study aims to analyze the effect of service quality and store design on retail competitiveness at Kopi Kenangan outlets in Cirebon City. This study uses an associative quantitative approach with a data collection method through a questionnaire to 100 respondents selected using purposive sampling, namely customers who make direct transactions at the outlet. Data analysis was carried out using covariance-based Structural Equation Modeling (SEM) with the help of AMOS software. The results show that service quality has a positive and significant effect on retail competitiveness with a p-value of 0.020. In addition, store design is also proven to have a positive and significant effect on retail competitiveness with a very high level of significance (p < 0.001) and is the most dominant variable. Simultaneously, service quality and store design are able to explain retail competitiveness by 55.3% (R² = 0.553). These findings prove that improving service quality and standardizing shop design are important strategies to strengthen Kopi Kenangan's position in facing competition in the coffee shop industry in Cirebon City.